Effects of Chronic Inhalation of Electronic Cigarette Vapor Containing Nicotine on Neurotransmitters in the Frontal Cortex and Striatum of C57BL/6 Mice - Alasmari, Fawaz; Crotty Alexander, Laura E.; Hammad, Alaa M.; Bojanowski, Christine M.; Moshensky, Alex; Sari, Youssef (Frontiers in Pharmacology, 2019)
Electronic (E)-cigarettes are the latest form of nicotine delivery device, and are highly popular in the general population. It is currently unknown whether vaping E-cigarettes (E-CIGs) leads to nicotine addiction. Alterations in the levels of the neurotransmitters in the mesocorticolimbic areas have been reported to mediate the initiation and development of nicotine addiction. Therefore, to determine whether E-cigarettes activate the same addiction pathways as conventional cigarettes, we investigated for the effects of daily inhalation of nicotine (24 mg/mL) containing E-CIG vapor for six-months on the concentrations of these neurotransmitters in the frontal cortex (FC) and striatum (STR) of male C57BL/6 mice as compared to control group that was exposed to air only. We reported here that six–month E-cigarette vapor-containing nicotine inhalation decreased dopamine concentration only in the STR. There were no changes in serotonin concentrations in the FC or STR. Chronic E-cigarette exposure also increased glutamate concentration in the STR alone, while glutamine concentrations were increased in both the FC and STR. We found that E-cigarette exposure also decreased GABA concentration only in the FC. These data suggest that chronic E-cigarette use alters homeostasis of several neurotransmitters in the mesocorticolimbic areas, which may result in the development of nicotine dependence in E-CIG users.